Chicha music as an advertising resource to arouse emotions in the consumer - Duran-Palomino, Ana Kelly (2022)
This study aims to analyze the emotions aroused by tropical Andean music—popularly known as chicha—present in the advertising of a well-known beverage brand in university students. The power music exerts in advertising is already commonly known as well as how it can intensify the effect of the message and trigger an emotional reaction in the consumer. This Peruvian musical genre is usually closely related to Peruvian identity and attributes of its population such as racial and cultural intermixing, creativity and self-improvement. In recent years, this sound resource has been established in the commercial communication of Peruvian brands aimed at the modern neo-Limenian; many of them descendants of migrants, proud of their origin and culture. This study is qualitative with a phenomenological approach. Through 16 interviews, the study shows how the presence of this musical genre can arouse positive emotions in the sample. In addition, the choice of music has to be coherent with the narrative structure of the advertising message to ensure optimal emotions.